Antibacterial, Antioxidant Properties and Bioactive Compounds of Thai Cultivated Mushroom Extracts Against Food-borne Bacterial Strains - Mathurot Chaiharn (Science Faculty of Chiang Mai University, 2019)
A fine-dried edible mushroom was extracted and investigated for its antibacterial activity against food-borne pathogenic bacteria, i.e. Bacillus cereus, Enterobacter aerogenes, Escherichia coli, Micrococcus luteus, Proteus vulgaris, Salmonella typhimurium and Staphylococcus aureus. The extracts of Flammulina velutipes, Ganoderma lucidum, Pleurotus ostreatus and Pleurotus pulmonarius inhibited both Gram-positive and Gram-negative bacteria. Water extract of Pleurotus pulmonarius significantly inhibited the growth of Gram-positive, i.e. Bacillus cereus and Micrococcus luteus (15 mm), while Gram-negative, i.e. Escherichia coli and Salmonella typhimurium resisted to most extracts. Only water extract from Pleurotus pulmonarius showed antibacterial activity against all tested bacteria. The minimum inhibitory concentrations (MICs) of Bacillus cereus had the lowest MIC range (1.25-5.00 mg/ml), whereas those of Salmonella typhimurium had the highest MICs (12.5-22.5 mg/ml) in Flammulina velutipes in ethylacetate extract, Ganoderma lucidum in methanol extract, Pleurotus ostreatus in ethylacetate extract and Pleurotus pulmonarius in water extract. Mushroom crude extracts were investigated for antioxidant capacity using the ABTS system. Results showed an effective antioxidant activity against ABTS radicals (91-94 %) and vitamin E derivatives (97 %), respectively. The IC50 values of Ganoderma lucidum, Pleurotus pulmonarius and Flammulina velutipes were 2.81 ± 0.02 mg/ml to 10.57 ± 0.27 mg/ml. Ganoderma lucidum exhibited maximum antioxidant potential as compared to Pleurotus pulmonarius and Flammulina velutipes, respectively. Positive correlations were found between total phenolic content in the mushroom extracts and their antioxidant activities. Water-extracted bioactive compounds produced by Pleurotus pulmonarius were characterized and identified on the basis of 1H-NMR as a polysaccharide. The study reveals that cultivated mushroom extracts have higher free radical scavenging potential with high levels of antioxidant compounds. These compounds showed broad-spectrum activity, were non-toxic, and might be applicable for human use. Results suggest that cultivated mushrooms may have potential as natural antibacterial and antioxidant properties and could be used as potential natural source for the development of nutraceuticals.